Medicinal herbs from Western Himalayas for hemorrhoids treatment: A review correlating traditional knowledge with modern therapeutics - Sakshi Dhiman; Rohit Kumar Nadda; Prerna Bhardwaj (Elsevier, 2023)
Background: Hemorrhoid or piles is a highly prevalent anorectal disease. In this review we aimed for systematic correlation of traditional claims of Himalayan medicinal plants with scientific investigation for Hemorrhoids. Methods: Detailed data on medicinal plants used for hemorrhoids, treatment options and traditional & scientific information on hemorrhoids are collected from research articles, review articles, books and pharmacopoeia. Literature survey was conducted using keywords hemorrhoids, Himalayan medicinal plants, medicine systems and hemorrhoids, traditional plants for hemorrhoids etc. The information is compiled from various sources such as PubMed, Hinari, science direct, google, google scholar, survey, and literature available on these plants and different books. Result: According to the traditional medicine knowledge, indigenous peoples of Western Himalayas and Chinese provinces are employing Terminalia chebula, Aristolochia contorta and Holarrhena antidysenterica for the treatment of piles. The Ayurvedic literature and TCM suggested some anti-hemorrhoidal formulations Diyu Huaijiao, Mayinglong Shexiang Zhichuang Gao (ointment), Kutajarishta. Among all the plants mentioned in formulations, Emblica officinalis, Terminalia chebula and Azadirachta indica were found promising in scientific investigations on piles and its pathological conditions. Phytoconstituents gallic acid, ferulic acid and steroidal alkaloids also revealed their efficacy against hemorrhoids and associated pathologies. Conclusion: By doing so, we discovered several valuable leads and gaps in the available literature. The identified medicinal plants and bioactive constituents may be evaluated against a standardized hemorrhoids model using a target-based approach.